Silk Hydrogel-Mediated Delivery of Bone Morphogenetic Protein 7 Directly to Subcutaneous White Adipose Tissue Increases Browning and Energy Expenditure - Townsend, Kristy L.; Pritchard, Eleanor; Coburn, Jeannine M.; Kwon, Young Mi; Blaszkiewicz, Magdalena; Lynes, Matthew D.; Kaplan, David L.; Tseng, Yu-Hua (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: Increasing the mass and/or activity of brown adipose tissue (BAT) is one promising avenue for treating obesity and related metabolic conditions, given that BAT has a high potential for energy expenditure and is capable of improving glucose and lipid homeostasis. BAT occurs either in discrete ‘classical’ depots, or interspersed in white adipose tissue (WAT), termed ‘inducible/recruitable’ BAT, or ‘beige/brite’ adipocytes. We and others have demonstrated that bone morphogenetic protein 7 (BMP7) induces brown adipogenesis in committed and uncommitted progenitor cells, resulting in increased energy expenditure and reduced weight gain in mice. BMP7 is therefore a reliable growth factor to induce browning of WAT. Methods: In this study, we sought to deliver BMP7 specifically to subcutaneous (sc)WAT in order to induce tissue-resident progenitor cells to differentiate into energy-expending recruitable brown adipocytes, without off-target effects like bone formation, which can occur when BMPs are in the presence of bone progenitor cells (outside of WAT). BMP7 delivery directly to WAT may also promote tissue innervation, or directly activate mitochondrial activity in brown adipocytes, as we have demonstrated previously. We utilized silk protein in the form of an injectable hydrogel carrying BMP7. Silk scaffolds are useful for in vivo delivery of substances due to favorable material properties, including controlled release of therapeutic proteins in an active form, biocompatibility with minimal immunogenic response, and prior FDA approval for some medical materials. For this study, the silk was engineered to meet desirable release kinetics for BMP7 in order to mimic our prior in vitro brown adipocyte differentiation studies. Fluorescently-labeled silk hydrogel loaded with BMP7 was directly injected into WAT through the skin and monitored by non-invasive in vivo whole body imaging, including in UCP1-luciferase reporter mice, thereby enabling an approach translatable to humans. Results: Injection of the BMP7-loaded silk hydrogels into the subcutaneous WAT of mice resulted in ‘browning’, including the development of multilocular, uncoupling protein 1 (UCP1)-positive brown adipocytes, and an increase in whole-body energy expenditure and skin temperature. In diet-induced obese mice, BMP7-loaded silk delivery to subcutaneous WAT resulted in less weight gain, reduced circulating glucose and lower respiratory exchange ratio (RER).